Scoring alien worlds: world music mashups in 21st century sci-fi and fantasy TV, film and video games - Stock, Jonathan P. J. (Tanjong Malim, 2021)
Scoring alien worlds: world music mashups in 21st century sci-fi and fantasy TV, film and video games by Stock, Jonathan P. J.